Interoperable geoprocessing services on the French hydrographical network and finalised application. (2017) - Mauclerc, Anthony; Coudercy, Laurent; Fauvet, Nicolas; Morel, Olivier; Mardhel, Vincent
This paper focuses on a set of geoprocessing services that were developed and are now exposed in an interoperable way (compliant with OGC WPS standard) to publicly offer basic operations on the French hydrographical network (e.g., computing the upstream/downstream of a river). Both organisational and architectural issues are discussed. In a second part, the way those services are now used and chained with other components in finalised solutions is detailed. More specifically, this point is illustrated through integration in an application dealing with ecological continuity issues, or, in other words: how to help experts to identify and prioritise the most appropriate set of flow barriers (mills, dams...) to equip or remove with respect to a given budget in order to improve the overall continuity. This last example is entirely based on interoperable components and gives a valuable feedback on building a whole architecture on such services.